THE PATTERN OF TRANSLATION STRATEGIES OF IDIOMATIC EXPRESSION IN COMICS - wisudawanto, rahmat (Lingual Journal of Language and Culture; Vol 9 No 1 (2020): Lingual: Journal of Language and Culture, 2020)
This article focuses on translation strategy of idiom in comic Garfield Goes to and its translation. It is expected to identify translation strategies and to know the pattern of translation strategies in translating the idiomatic expression. This research belongs to descriptive qualitative. The source of data is a comic entitled Garfield Goes to Waist and its translation Garfield Mengurangi Berat. Whereas, the data are all of idioms found in the comic. This research applies total sampling technique since the samples are all of data which are found in the source of data. The result of the analysis shows that there are four strategies used by the translator in translating idioms. Meanwhile, the pattern of strategies indicates that Translation by Paraphrasing is dominant strategy. Besides, the others strategies are translation Using an Idiom of Similar Meaning but Dissimilar Form, Translation by Omission and Using an Idiom of Similar Meaning and Form respectively